The consequences of chronic kidney disease on bone metabolism and growth in children - Bacchetta, Justine (Oxford University Press, 2012)
Growth retardation, decreased final height and renal osteodystrophy (ROD) are common complications of childhood chronic kidney disease (CKD), resulting from a combination of abnormalities in the growth hormone (GH) axis, vitamin D deficiency, hyperparathyroidism, hypogonadism, inadequate nutrition, cachexia and drug toxicity. The impact of CKD-associated bone and mineral disorders (CKD–MBD) may be immediate (serum phosphate/calcium disequilibrium) or delayed (poor growth, ROD, fractures, vascular calcifications, increased morbidity and mortality). In 2012, the clinical management of CKD–MBD in children needs to focus on three main objectives: (i) to provide an optimal growth in order to maximize the final height with an early management with recombinant GH therapy when required, (ii) to equilibrate calcium/phosphate metabolism so as to obtain acceptable bone quality and cardiovascular status and (iii) to correct all metabolic and clinical abnormalities that can worsen bone disease, growth and cardiovascular disease, i.e. metabolic acidosis, anaemia, malnutrition and 25(OH)vitamin D deficiency. The aim of this review is to provide an overview of the mineral, bone and vascular abnormalities associated with CKD in children in terms of pathophysiology, diagnosis and clinical management.